Avaliação do Exoma no megaureter - Augusto César Soares dos Santos Junior (2015)
Congenital anomalies of the kidney and urinary tract (CAKUT) represent a broad range of disorders that result from abnormalities of the urinary collecting system, abnormal embryonic migration of the kidneys or abnormal renal parenchyma development. Megaureter constitutes one of the phenotypes of CAKUT and represents a condition whereby the diameter of the ureter is abnormally dilated. Currently, much is beingstudied regarding the pathogenesis of CAKUT. While many CAKUT cases are apparently sporadic, familial clustering is common, suggesting that CAKUT pathogenesis is influenced by genetic factors. Some authors have hypothesized that variations in specific regions of the genome could imbalance the mechanisms involved in the expressions of cytokines needed to modulate the ureter morphogenesis and thusresult in the development of megaureter. Despite this hypothesis, its still unknown to what extent environmental or genetic factors are implicated. Therefore, this study aimed to investigate a pair of monozygotic twins discordant for the expression of bilateral congenital megaureter for the presence of genetic variations using the whole exome technique. This study also included a set of 11 non-related individuals with a confirmeddiagnosis of congenital megaureter. All patients were recruited from June 2012 to June 2013 at the Pediatric Nephrology Unit, Hospital Bias Fortes, at UFMG. This study followed the Declaration of Helsinki and was approved the local ethics committee. After applying filters for SNVs prioritization we identified 81 SNVs present exclusively in the proband compared to his family and 5 SNVs present exclusively in the probandand in common to the pool of non-related megaureter patients. After using the STRING tool we prioritize the SNVs found in the genes TBX3, GATA6, GATA1, DHH, ACVRL1 and SOX2 for validation using the Sanger technic. The SNVs found at the genes TBX3, GATA6 and DHH were not confirmed in the proband. Validation of SNVs identified at the genes GATA1, ACVRL1 and SOX2 are in progress. There is still a long way to go before we fully uncover the mechanisms involved in the development the megaureter. This study has taken one step closer in identifying candidate genes involved in the genesis of megaureter.